Patrimônio desvelado: história e memória afro-brasileira no patrimônio cultural de Jaraguá/GO - Correia, Elilza Rodrigues (2025)
This research aims to develop a proposal for History teaching based on the Heritage Education methodology, articulated with the Guidelines for Ethnic-Racial Relations Education. Through the study and problematization of the cultural heritage of Jaraguá/GO, it seeks to identify and understand the representations and silences involving the history and memory of the local AfroBrazilian population. The investigation analyzes how power relations influence the construction of historical narratives and the valorization (or marginalization) of tangible and intangible cultural heritage associated with the Afro-descendant community. As a result, the research proposes educational material for teachers and students in basic education, especially those in the final years of elementary school and in high school, structured in an interactive map that presents spaces in the city’s historic center related to Afro-Brazilian history, promoting a critical approach to local history.